EVI1 expression predicts outcome in higher-risk myelodysplastic syndrome patients. Issue 12 (2nd December 2018) - Liu, Lin; Wang, Jinhuan; Jiang, Yanan; Xie, Huan; Tang, Xiaoqiong; Li, Qiubai; Wang, Huaquan; Zou, Ping; Miao, Zhaoyi; Lv, Yangyang; Wang, Haitao; Cao, Zeng; et al.
Abstract: The clinical impact of ecotropic viral integration site 1 ( EVI1 ) expression status in myelodysplastic syndromes (MDS) is poorly defined. Here, we investigate the expression of EVI1 and its associated clinical and cytogenetic characteristics in 398 MDS patients. High EVI1 levels ( EVI1 high ) were found more frequently in Higher-risk MDS patients. Other cytogenetic abnormalities over-represented among EVI1 high cases included complex karyotype, del(5q), monosomy 7, and 12q-compared with EVI1 low MDS. No specific gene mutation was found different between EVI1 high and EVI1 low patients, except for a high proportion of TP53 mutation in the EVI1 high group. For EVI high patients, mean number of gene mutations was higher than that in EVI1 low patients. No definite correlation was found between EVI1 expression and MDS prognosis. However, for Higher-risk MDS patients, EVI1 high patients have poorer survival rate compared with EVI1 low patients. Moreover, EVI1 high was an adverse prognostic marker for MDS with excess blasts subtype. The addition of EVI1 could deteriorate the survival of MDS patients with chromosome 3 abnormalities, del(5q-) or monosomy 7. Taken together, EVI1 overexpression is a poor prognostic marker for higher-risk MDS group and could be included in risk stratification for MDS patients.